Sawtooth mixing of alphas, knock-on D, and T ions, and its influence on NPA spectra in ITER plasma. (3rd July 2018) - Mironov, M.I.; Zaitsev, F.S.; Gorelenkov, N.N.; Afanasyev, V.I.; Chernyshev, F.V.; Nesenevich, V.G.; Petrov, M.P.
Abstract: Sawtooth mixing of fast ions is considered in ITER for plasma parameters close to the inductive 15 MA scenario. New mixing formula is presented for a drift trajectory averaged distribution function (DF) of fast passing and trapped ions. This formula generalizes Kadomtsev's model for the case of non-circular magnetic surfaces, arbitrary aspect ratio, and significant deviations of charged particle drift trajectories from the magnetic flux surfaces, and can be applicable to a wide class of instabilities. Generalized formulae are implemented in the Fokker–Planck package three-dimensional (FPP-3D) code. FPP-3D is applied for calculation of the fast alpha-particle (He 4 ), deuterium (D), and tritium (T) DFs. Simulations take into account D and T nuclear elastic scattering (NES or knock-on) by fast He 4 . Changes in the radial profile of He 4 power deposition to the thermal plasma in the presence of plasma mixing are estimated. An effective tool for fast ion studies in ITER will be a system of neutral particle analyzers (NPA) since it allows direct measurements of the fast hydrogen ions' DF inside the plasma. The main NPA goal on ITER is to measure the D/T fuel isotope ratio in the plasma core with the use of D and T atom spectra in the MeV range. The spectra and their sensitivity to sawtooth mixing are calculated. It was found that ITER NPA allows us to detect those oscillations. Simulations show the possibility of determining the D/T ratio with NPA regardless of whether sawtooth oscillations exist.